A63: Treatment of Arthritis in Animal Models of the Mucopolysaccharidoses Using a Novel Anti‐Inflammatory Drug, Pentosan Polysulfate. Issue 11 (March 2014) - Simonaro, Calogera; Frohbergh, Michael; Ge, Yi; Meng, Fanli; Schuchman, Edward
Abstract : Background/Purpose: The mucopolysaccharidoses (MPS) comprise a group of 11 lysosomal storage disorders (LSDs) due to inherited deficiencies of glycosaminoglycan (GAG) degrading enzymes. Naturally occurring animal models exist for most of these disorders, providing excellent systems in which to study disease pathogenesis and treatment. We have previously shown that GAG storage in MPS leads to activation of the TLR4/TNF‐alpha inflammatory pathway, and that inflammation is a major contributor to the degenerative cartilage disease occurring in MPS patients. The pattern of inflammatory changes in MPS closely resembles that occurring in arthritis, and the MPS animals also represent excellent, naturally occurring genetic models of arthritis. Various treatment approaches have been investigated for MPS, and we recently identified one FDA‐approved drug, pentosan polysulfate (PPS), that resulted in remarkable clinical improvements in a rat model of MPS type VI (Schuchman et al., PLoS One, 2013). Methods: In our previous work we reported the effects of daily oral PPS treatment in MPS VI rats, and here we compare these effects with weekly subcutaneous (subQ) injections. Four groups of MPS VI rats were treated with weekly subQ PPS at human equivalent doses of 1, 2 and 4 mg/kg, and with a combination of 2 mg/kg PPS and 1 mg/kg enzyme replacement therapy (ERT; Naglazyme®). Results: The most efficacious subQ PPS dose was 2 mg/kg. Among the four groups of treated rats the best results were found in animals treated with a combination of PPS and ERT. Treatment of all MPS VI rats with weekly subQ PPS for up to 6 months was safe. Conclusion: We propose that weekly subQ injections of PPS will be efficacious and safe in MPS patients, and a phase 1/2 clinical study is planned. We also propose that PPS could be effective in arthritis, and might provide a cost‐effective, safe alternative to existing TNF‐alpha drugs.